CONSTRUCTING A SCALE OF COMMUNICATION SOURCES (KINETIC AND SOCIAL) AND ITS RELATIONSHIP TO REACTION DURING PASSING AMONG FIRST DIVISION FOOTBALL PLAYERS IN IRAQI LEAGUE FOR 2022-2023 SPORTS SEASON - Maitham Mutair Hamidi Al-Krizi (Universitas Negeri Jakarta, 2024)
Background. Effective communication during football tackles is crucial for team coordination and individual performance. Communication can occur through both kinetic (motor-based) and social (interpersonal) channels, which may influence players’ motor response speed. Objectives. This study aimed to develop two measurement scales for communication sources—kinetic and social—during tackling situations in football, and to establish a scale for motor response speed. It also sought to examine the relationship between these communication sources and motor response speed among first division football players in the Iraqi League during the 2022–2023 season. Method. A descriptive research approach was adopted using the survey method. The exploratory study involved 24 players (18.75%), while the main study was conducted on 104 players (81.75%) from six clubs. The largest participation came from Maysan Club (19.5%), followed by Al-Bahri (18%), Al-Kufa (17.2%), Al-Nasiriyah (16.4%), Afak (14.8%), and Al-Samawa (14.1%). The researcher constructed scales based on the following dimensions: self-denial, mental preparation, self-confidence, attention focus, motor sensation, and feedback, alongside a motor response speed scale. Appropriate statistical techniques were used for analysis. Results. The results indicated that the two developed scales effectively measure communication sources and motor response speed. A significant relationship was found between communication sources and players’ motor response speed during football tackles. Conclusion. The findings highlight the importance of assessing both kinetic and social communication sources to better understand and enhance players’ response speeds. It is recommended to integrate modern training methods that strengthen communication and motor coordination, and to involve experts in educational, psychological, and social sciences in sports training to support optimal team communication and performance during matches.